The great big book of horrible things : the definitive chronicle of history's 100 worst atrocities - White, Matthew (W.W. Norton, 2012)
Evangelists of human progress meet their opposite in Matthew White's epic examination of history's one hundred most violent events, or, in White's piquant phrasing, "the numbers that people want to argue about." Reaching back to 480 BCE's second Persian War, White moves chronologically through history to this century's war in the Congo and devotes chapters to each event.